The Program of Psychological and Pedagogical Activity within the Framework of a Consulting and Methodological Point in a Preschool Educational Organization - Pinigina, I.A.; Seliverstova, J.V.; Smolnikova, M.F.; Timoshenko, N.V. (Bulletin of Practical Psychology of Education, 2021)
The program of psychological and pedagogical activity within the framework of the consultative and methodological post (hereinafter referred to as the CMP) in the preschool educational organization has been developed in accordance with the requirements of the federal state educational standard for preschool education (hereinafter referred to as the FSES PE) and the Sanitary Rules and Regulations (hereinafter referred to as the SanRR) to provide advisory — methodological assistance to parents of children of early preschool age who do not attend preschool. The main priority areas in the activities of the CMP are: conducting psychological and pedagogical diagnostics of the development of preschool children who do not attend preschool; information and educational work with parents of preschool children who do not attend preschool; organization of educational and correctional and developmental work with preschool children who do not attend preschool education. This program has been successfully tested on the basis of the CMP of the center of earlier development of kindergarten No. 172 in the city of Tyumen. The approbation showed that the level of cognitive activity, independence and creativity in children increased significantly; children learned to interact better with each other. For children attending the CMP, the adaptation process when entering kindergarten proceeds as successfully, quickly and painlessly as possible. A genuine interest in the activities of children in kindergarten was shown by parents, who became more interested in how to properly organize the upbringing and educational process at home. Parents themselves gradually began to get involved in the educational process. The kindergarten has become a place for them where they can receive qualified help. Trust in teachers has grown, a desire to discuss with them the problems of raising children. Программа психолого-педагогической деятельности в рамках консультативно-методического пункта (далее — КМП) в дошкольной образовательной организации разработана в соответствии с требованиями федерального государственного образовательного стандарта дошкольного образования (далее — ФГОС ДО) и Санитарными правилами и нормами (далее — СанПиН) для оказания консультативно-методической помощи родителям детей раннего дошкольного возраста, не посещающих ДОО. Основными приоритетными направлениями в деятельности КМП являются: проведение психолого-педагогической диагностики развития детей дошкольного возраста, не посещающих ДОО; информационно-просветительская работа с родителями детей дошкольного возраста, не посещающих ДОО; организация образовательной и коррекционно-развивающей работы с детьми дошкольного возраста, не посещающими ДОО. Данная программа прошла успешную апробацию на базе КМП МАДОУ «Центр развития ребенка — детский сад № 172» города Тюмени. Апробация показала, что у детей существенно вырос уровень познавательной активности, самостоятельности и креативности; дети научились лучше взаимодействовать друг с другом. У детей, посещающих КМП, процесс адаптации при поступлении в детский сад протекает максимально успешно, быстро и безболезненно. Неподдельный интерес к деятельности детей в детском саду проявили родители, которые стали больше интересоваться, как правильно организовать воспитательно-образовательный процесс дома. Родители постепенно сами начали втягиваться в образовательный процесс. Детский сад для них стал местом, где они могут получить квалифицированную помощь. Выросло доверие к педагогам, желание обсуждать с ними проблемы воспитания детей.